Incidental findings on whole‐body computed tomography in trauma patients: the current state of incidental findings and the effect of implementation of a feedback system. Issue 3 (27th March 2019) - Kumada, Keisuke; Murakami, Nobuo; Okada, Hideshi; Toyoda, Izumi; Ogura, Shinji; Asano, Takahiko
Abstract : Aim: Whole‐body computed tomography (CT) for trauma occasionally reveals significant incidental findings not related to trauma, which require an adequate response. In this study, we examined the current state of incidental findings in trauma patients on whole‐body CT and the effects of the feedback system. Methods: The subject sample included trauma patients who underwent whole‐body CT while being examined for trauma during the 2‐year period, with the interpretation of the CT reported by a radiologist. The frequency and recognition of incidental findings and the involved body region were investigated. The state of incidental findings before and after implementation of a radiography report feedback system was also examined. Results: During the study period, whole‐body CT revealed incidental findings in 79 of 199 trauma patients (40.1%). The mean age of the 79 patients with incidental findings was 62.8 ± 19.5 years, and the mean injury severity score was 16.6 ± 10.0. No difference was observed in the severity of trauma, age, or length of hospital stay. The incidental findings were related to the liver/gallbladder in 22 patients, kidneys in 17, lungs in 14, and the intracranial area in 13. The recognition rate of incidental findings after the implementation of the feedback system increased from 23.3% to 32.6%. Conclusions: Considering that not all incidental findings are accurately recognized, a proper feedback system is required. A feedback system is beneficial and a need to ensure improvement in the recognition of incidental findings. Abstract : Whole‐body computed tomography for trauma in some cases reveals significant incidental findings that are not related to trauma but require an adequate response.